Development of stylistic exercise and becoming media linguistics in Belarus - Ivchenkov, Viktor I. (Journal of the Belarusian State University. Journalism, 2019)
The conditions of formation and characteristics of media linguistics in Belarus, the path traced by the study of stylistic  phenomena in the texts of the media to the media discourse analysis, defined ontology of such interaction, revealed the role of binding style and rhetoric in the study of language as a social fact of action. Showing the historical connection of language  learning and the media style of Soviet scientists with the works of modern medialingvistov, special attention is paid to the  creative heritage of Professor M. E. Tikotskii, his interpretation of styles and theories of journalism as a special kind of social  and political literature. Revealed significant differences in the teaching of language and style of the media in the faculties of  journalism and philology, justified by the nature of media text rechevedcheskaya study, set priorities media linguistics in the  integrated treatment of stylistic and social phenomena.
Keywords: media linguistics; style; text; discursive analysis of media; journalism